Impact of long trains on the railway track - V. S. Kossov; A. A. Lunin; Y. A. Panin; A. V. Trifonov; I. E. Il’In (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The article presents results of pilot and theoretical studies of JSC VNIKTI in the field of interaction of railway track and a rolling stock and perspective of their application. Questions of longitudinal dynamics in the conditions of different types of braking of trains of increased weight and lengths and their influence on infrastructure are considered. Analysis of dynamic qualities and indicators of impact of model of coupled trainset on track is carried out by means of computer modeling, and impact evaluation of action of longitudinal force on carriage indicators, both dynamic and by impact on track, is given at different conditions of railway track. As a result of testing in 2015 of doubled trains weighing up to 14,200 tonnes at various types of braking the following conclusions were obtained: 1. The considerable array of experimental data on interaction of a rolling stock and way at emergency braking is received allowing a quantitative assessment to this process. 2. When performing asynchronous emergency brakings the “practical top” of the compressive forces in the train (1600 kN) has been for the first time reached and the moment of loss of stability of a rolling stock in a rail gauge has been recorded. 3. When performing synchronous braking sufficient stability of the conducted locomotive and nearby the standing car is confirmed at influence of longitudinal forces. 4. The received results of pilot and theoretical studies can be used for modification of normative documentation for development of local instructions for safe driving of the coupled trains, and furthermore at the organization of pilot trips of the coupled trains of higher weight.